Electrolyte-resistant double-sided tape for environment-friendly new energy lithium battery
By using specific formulas of electrolyte-resistant adhesives and crosslinking agents, a film layer with macromolecular substances with silicon-oxygen bonds is formed, which solves the problems of poor electrolyte resistance and high-temperature aging in lithium battery packaging, and achieves excellent high-temperature resistance and electrolyte resistance of the tape.
Patent Information
- Application Number
- CN202411743924.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-30
- Publication Date
- 2025-03-07
AI Technical Summary
Traditional double-sided tape has problems such as poor electrolyte resistance and high temperature aging during lithium battery packaging, which may lead to degradation of battery performance and safety hazards.
Using an electrolyte resistant adhesive including methyl methacrylate, hydroxyethyl methacrylate, acrylic acid, isooctyl acrylate and organic solvents, a film layer of macromolecular substances with alternating structures of silicon-oxygen bonds and cyclohexylhexafluoropropane-tert-butyl blocks is formed through the preparation of crosslinking agents and the coating and curing process of adhesives.
The cohesive energy and bonding properties of the adhesive are improved, and its high temperature and electrolyte resistance are enhanced, so that the prepared double-sided tape can show excellent comprehensive performance.
Smart Images

Figure CN119570386A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of adhesive tapes, and in particular to an electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries. Background Art
[0002] With the increasing attention paid to environmental protection and sustainable development around the world, the new energy industry has developed rapidly. As an important component of the new energy field, lithium batteries have been widely used in electric vehicles, energy storage systems, portable electronic devices and other fields. However, a large number of auxiliary materials are required in the manufacturing and packaging of lithium batteries. Among them, double-sided tape, as an important packaging material, has a significant impact on the performance and safety of lithium batteries.
[0003] In the packaging process of lithium batteries, double-sided tape is mainly used to fix battery cells, prevent electrolyte leakage, and isolate the direct contact between the inside of the battery and the external environment. Through reasonable tape design, the packaging efficiency and reliability of lithium batteries can be effectively improved, and production costs can be reduced. Traditional double-sided tape mainly uses acrylic adhesive as the raw material of the tape film layer. This type of tape has some problems in the lithium battery packaging process, such as poor electrolyte resistance and easy aging at high temperatures. These problems may cause electrolyte leakage, battery performance degradation, and even safety problems during long-term use of the battery.
[0004] Based on this, the development of double-sided tape with excellent electrolytic resistance and high temperature resistance is of great significance to the sustainable development of lithium batteries. Summary of the invention
[0005] 1. Technical issues to be resolved
[0006] In view of the deficiencies in the prior art, the present invention provides an electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries.
[0007] (II) Technical solution
[0008] An electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries, comprising a base film layer, an adhesive film layer and a release film; the adhesive film layer is distributed on both sides of the base film layer; the release film is distributed on both sides of the adhesive film layer; the adhesive film layer is formed by coating an electrolyte-resistant adhesive on both sides of the base film layer and curing; the electrolyte-resistant adhesive is made of raw materials including the following parts by weight:
[0009]
[0010] The preparation method of the electrolyte resistant adhesive comprises the following steps:
[0011] Step 1: Mix methyl methacrylate, hydroxyethyl methacrylate, acrylic acid, isooctyl acrylate and an organic solvent, and after they are completely dissolved to form a uniform reaction solution, introduce nitrogen for protection, then raise the temperature to 80-83° C., and then add the initiator to the reaction solution. After the addition is completed, heat and stir for 4-8 hours to form a prepolymer;
[0012] Step 2: Lower the temperature to 60-65°C, then add the cross-linking agent to the reaction solution, then raise the temperature to 82-85°C, continue to keep warm for 8-12 hours, remove the nitrogen, stop heating, and add the curing agent after it drops to room temperature, stir evenly, and discharge the material to obtain the electrolyte-resistant adhesive.
[0013] As a further embodiment of the present invention, the method for preparing the double-sided tape comprises the following steps:
[0014] The first step is to use a precision coating machine to apply the electrolyte resistant adhesive on one side of the PET base film layer, and control the coating amount to 10-15g / cm 2 , then placed in an oven, controlled at 100-120°C, wait for the adhesive to solidify to form a film layer, and then attach non-silicon release paper to the outside of the film layer to form a release film;
[0015] In the second step, the same operation as in the first step is performed on the other side of the PET base film layer to obtain a double-sided tape.
[0016] As a further embodiment of the present invention, the specific preparation method of the cross-linking agent comprises the following steps:
[0017] Step S1, nitrogen is introduced into the polymerization kettle, and then 2,2-bis(4-hydroxycyclohexyl)hexafluoropropane and toluene are added, stirring is started, and then di-tert-butylchlorosilane is added into the polymerization kettle. After the addition is completed, the temperature is increased to 70-80° C., and after stirring for 1-3 hours, an acid binding agent is added into the polymerization kettle, and stirring is continued for 8-12 hours. The solvent is evaporated, and the temperature is lowered and the material is discharged to obtain an intermediate polymer;
[0018] Step S2, adding the intermediate polymer and the terminal modifier into tetrahydrofuran, stirring mechanically, and then adding the phase transfer catalyst, and then raising the temperature to 60-70°C, stirring at the temperature for 2-4 hours, cooling and discharging the material, and the crosslinking agent can be obtained.
[0019] As a further embodiment of the present invention, in step S1, the molar ratio of 2,2-bis(4-hydroxycyclohexyl)hexafluoropropane to di-tert-butylchlorosilane is 1:0.8-0.9.
[0020] As a further embodiment of the present invention, in step S1, the acid binding agent is triethylamine.
[0021] As a further embodiment of the present invention, in step S2, the terminal group modifier is glycidyl methacrylate or glycidyl acrylate.
[0022] As a further embodiment of the present invention, in step S2, the phase transfer catalyst is boron trifluoride etherate complex.
[0023] By adopting the above technical scheme, 2,2-bis(4-hydroxycyclohexyl)hexafluoropropane and di-tert-butylchlorosilane are used as polymerization monomers. Since the active hydroxyl groups and Si-Cl between them can produce substitution reactions, and an acid binding agent is used for catalysis, continuous substitution reactions can occur between them to form a macromolecular substance connected by Si-O bonds and having a block alternating structure. By controlling the dosage ratio between them, the obtained intermediate polymer is hydroxyl-terminated. Then, an end group modifier is used to modify the terminal hydroxyl groups of the intermediate polymer under the action of a phase transfer catalyst, and the active hydroxyl end-capping is converted into an unsaturated olefin end-capping to obtain a crosslinking agent.
[0024] As a further embodiment of the present invention, the initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
[0025] As a further embodiment of the present invention, the organic solvent is ethyl acetate or toluene.
[0026] As a further embodiment of the present invention, the curing agent is an aziridine curing agent or an isocyanate curing agent.
[0027] (III) Beneficial technical effects
[0028] The present invention prepares a macromolecular substance connected by a silicon-oxygen bond and having a cyclohexylhexafluoropropane-tert-butyl block alternating structure as a crosslinking agent. First, the crosslinking effect of the crosslinking agent can greatly increase the crosslinking density of the prepared adhesive molecular chain, which not only improves the cohesive energy of the adhesive and enhances the bonding performance of the adhesive, but also limits the movement of the adhesive molecular chain, thereby improving the high temperature resistance of the adhesive. Secondly, the crosslinking agent structure contains a large number of high-bond energy silicon-oxygen bonds and rigid heterocyclic structures, which have a positive effect on improving the stability of the adhesive molecular chain and can also enhance the high temperature resistance of the adhesive. Moreover, the silicon-oxygen bonds, tert-butyl groups and fluorine-containing segments in the crosslinking agent molecular chain are extremely hydrophobic, which can prevent the electrolyte from penetrating into the inner layer of the adhesive, thereby improving the electrolyte resistance of the adhesive. Therefore, by uniquely designing the adhesive molecular chain, the prepared double-sided tape can exhibit excellent comprehensive properties such as high temperature resistance and electrolyte resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0030] Figure 1 This is the infrared analysis test diagram of the cross-linking agent. DETAILED DESCRIPTION
[0031] In order to facilitate the understanding of the present invention, the present invention will be described more fully below. Preferred embodiments of the present invention are given below. However, the present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.
[0032] Preparation Example 1
[0033] Preparation of cross-linking agent:
[0034] Step S1, nitrogen is introduced into the polymerization kettle, and then 0.4 g of 2,2-bis(4-hydroxycyclohexyl)hexafluoropropane and toluene are added, stirring is started, and then 0.9 g of di-tert-butylchlorosilane is added into the polymerization kettle. After the addition is completed, the temperature is increased to 75° C., and after stirring for 2 hours, 0.1 g of triethylamine is added into the polymerization kettle, and stirring is continued for 9 hours. The solvent is evaporated, and the temperature is lowered and the material is discharged to obtain an intermediate polymer;
[0035] Step S2, add 0.8g of the intermediate polymer and 0.1g of glycidyl methacrylate to tetrahydrofuran, stir mechanically, then add 0.02g of boron trifluoride ether complex, then increase the temperature to 65°C, keep stirring for 3h, cool and discharge, and the crosslinking agent can be obtained.
[0036] Figure 1 This is the infrared analysis test chart of the crosslinking agent, where 3267cm -1 The characteristic absorption peak at 3037cm is the characteristic absorption peak of hydroxyl group produced by the ring-opening reaction during end-capping. -1 The characteristic absorption peak at 1748 cm is the characteristic absorption peak of carbon-hydrogen of carbon-carbon double bond. -1 The characteristic absorption peak at 1000 cm is the C=O characteristic absorption peak in the structure of glycidyl methacrylate, a capping agent. -1 ~1100cm -1 The characteristic absorption peaks appearing at are the overlapping characteristic absorption peaks of ether bonds and silicon-oxygen bonds.
[0037] Example 1
[0038] Preparation of electrolyte resistant adhesive:
[0039] Step 1: According to the weight ratio, 50 parts of methyl methacrylate, 5 parts of hydroxyethyl methacrylate, 2 parts of acrylic acid, 15 parts of isooctyl acrylate and 150 parts of organic solvent ethyl acetate are stirred and mixed, and after they are completely dissolved to form a uniform reaction liquid, nitrogen is introduced for protection, and then the temperature is increased to 80° C., and 0.5 parts of initiator azobisisobutyronitrile is added to the reaction liquid. After the addition is completed, the mixture is stirred for 4 hours at the temperature to form a prepolymer;
[0040] Step 2: Lower the temperature to 60°C, then add 1 part of the cross-linking agent to the reaction solution, then raise the temperature to 82°C, continue to keep warm for 12 hours, remove the nitrogen, stop heating, and after it drops to room temperature, add 5 parts of the curing agent, stir evenly, and discharge the material to obtain the electrolyte-resistant adhesive.
[0041] The preparation method of the cross-linking agent is shown in Preparation Example 1; the curing agent is isophorone diisocyanate, and the following are the same.
[0042] Example 2
[0043] Preparation of electrolyte resistant adhesive:
[0044] Step 1: According to the weight ratio, 55 parts of methyl methacrylate, 6 parts of hydroxyethyl methacrylate, 3 parts of acrylic acid, 18 parts of isooctyl acrylate and 200 parts of organic solvent toluene are stirred and mixed, and after they are completely dissolved to form a uniform reaction liquid, nitrogen is introduced for protection, and then the temperature is raised to 82° C., and 1 part of initiator azobisisoheptanenitrile is added to the reaction liquid. After the addition is completed, the mixture is kept warm and stirred for 6 hours to form a prepolymer;
[0045] Step 2: Lower the temperature to 60°C, then add 2.5 parts of a cross-linking agent to the reaction solution, then raise the temperature to 83°C, continue to keep warm for 9 hours, remove the nitrogen, stop heating, and after it drops to room temperature, add 8 parts of a curing agent, stir evenly, and discharge the material to obtain an electrolyte-resistant adhesive.
[0046] Example 3
[0047] Preparation of electrolyte resistant adhesive:
[0048] Step 1: According to the weight ratio, 65 parts of methyl methacrylate, 10 parts of hydroxyethyl methacrylate, 6 parts of acrylic acid, 25 parts of isooctyl acrylate and 250 parts of organic solvent toluene are stirred and mixed, and after they are completely dissolved to form a uniform reaction liquid, nitrogen is introduced for protection, and then the temperature is raised to 83° C., and 1.5 parts of initiator azobisisobutyronitrile are added to the reaction liquid. After the addition is completed, the mixture is stirred for 8 hours at the temperature to form a prepolymer;
[0049] Step 2: Lower the temperature to 65°C, then add 3 parts of a cross-linking agent to the reaction solution, then raise the temperature to 85°C, continue to keep warm for 8 hours, remove the nitrogen, stop heating, and after it drops to room temperature, add 10 parts of a curing agent, stir evenly, and discharge the material to obtain an electrolyte-resistant adhesive.
[0050] Comparative Example 1
[0051] Preparation of electrolyte resistant adhesive:
[0052] Step 1: According to the weight ratio, 55 parts of methyl methacrylate, 6 parts of hydroxyethyl methacrylate, 3 parts of acrylic acid, 18 parts of isooctyl acrylate and 200 parts of organic solvent toluene are stirred and mixed, and after they are completely dissolved to form a uniform reaction liquid, nitrogen is introduced for protection, and then the temperature is raised to 82° C., and 1 part of initiator azobisisoheptanenitrile is added to the reaction liquid. After the addition is completed, the mixture is kept warm and stirred for 6 hours to form a prepolymer;
[0053] Step 2: Lower the temperature to 60°C, then add 2.5 parts of the cross-linking agent N,N'-methylenebisacrylamide to the reaction solution, then raise the temperature to 83°C, continue to keep warm for 9 hours, remove the nitrogen, stop heating, and after it drops to room temperature, add 8 parts of the curing agent, stir evenly, and discharge the material to obtain the adhesive.
[0054] Comparative Example 2
[0055] Preparation of electrolyte resistant adhesive:
[0056] According to weight proportions, 55 parts of methyl methacrylate, 6 parts of hydroxyethyl methacrylate, 3 parts of acrylic acid, 18 parts of isooctyl acrylate and 200 parts of organic solvent toluene are stirred and mixed. After they are completely dissolved to form a uniform reaction liquid, nitrogen is introduced for protection. Then the temperature is raised to 82°C, and 1 part of initiator azobisisoheptanenitrile is added to the reaction liquid. After the addition is completed, the mixture is stirred for 16 hours at a warm temperature. The nitrogen is removed and the heating is stopped. After the temperature drops to room temperature, 8 parts of curing agent are added, stirred evenly, and the material is discharged to obtain an adhesive.
[0057] Test Case
[0058] a. Apply the adhesives in the examples and comparative examples on the surface of the PET base film, and control the coating amount to 15 g / cm 2 , and then placed in an oven, controlled at 120°C, and after the adhesive is cured into a film, take out the sample and perform a peel strength test according to standard GB / T2792-2014;
[0059] b. Use the same batch of film test samples to bond two battery separators, then soak them in electrolyte at 85°C for one day and take them out to observe whether there is any shedding or bubbling to determine the electrolyte resistance of the adhesive;
[0060] The electrolyte has a solute of 1M lithium perchlorate trihydrate and a solvent of 1,2-propylene glycol carbonate and ethylene glycol dimethyl ether in a volume ratio of 1:1;
[0061] c. Place the test samples of the same batch of films in a temperature environment of 150°C, take them out after 4 hours, and observe whether the film surface is deformed, bulged, or has residual adhesive, to determine the high temperature resistance of the adhesive. The test results are recorded in the following table:
[0062]
[0063] Analysis shows that the adhesive prepared by cross-linking and polymerizing the cross-linking agent in Preparation Example 1 of the present invention with the acrylate monomer has the advantages of good bonding performance, excellent electrolyte resistance, and good high temperature resistance, and can be directly used to make double-sided tape for lithium batteries.
[0064] After the cross-linking agent is replaced with a conventional cross-linking agent, the adhesive molecular chain does not contain structures such as silicon-oxygen bonds, rigid heterocycles, and a large number of strongly hydrophobic segments, resulting in a significant impact on the adhesive's electrolyte resistance and high temperature resistance.
[0065] The adhesive in Example 2 of the present invention is used to prepare an electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries. The specific preparation method includes the following steps:
[0066] The first step is to use a precision coating machine to apply the electrolyte-resistant adhesive on one side of the PET base film layer, and control the coating amount to 15g / cm 2 , and then placed in an oven, controlled at 120°C, until the adhesive is cured to form a film layer, and then non-silicon release paper is attached to the outside of the film layer to form a release film;
[0067] In the second step, the same operation as in the first step is performed on the other side of the PET base film layer to obtain a double-sided tape.
[0068] Based on the ideal embodiment of the present invention, through the above description, relevant personnel can make various changes and modifications without departing from the technical concept of the present invention. The technical scope of the present invention is not limited to the content in the specification, and the technical scope must be determined according to the scope of the claims.
Claims
1. An electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries, characterized in that: It comprises a base film layer, an adhesive film layer and a release film; the adhesive film layer is distributed on both sides of the base film layer; the release film is distributed on both sides of the adhesive film layer; the adhesive film layer is formed by coating an electrolyte-resistant adhesive on both sides of the base film layer and curing; the electrolyte-resistant adhesive is made of raw materials including the following parts by weight: The preparation method of the electrolyte resistant adhesive comprises the following steps: Step 1: Mix methyl methacrylate, hydroxyethyl methacrylate, acrylic acid, isooctyl acrylate and an organic solvent, and after they are completely dissolved to form a uniform reaction solution, introduce nitrogen for protection, then raise the temperature to 80-83° C., and then add the initiator to the reaction solution. After the addition is completed, heat and stir for 4-8 hours to form a prepolymer; Step 2: Lower the temperature to 60-65°C, then add the cross-linking agent to the reaction solution, then raise the temperature to 82-85°C, continue to keep warm for 8-12 hours, remove the nitrogen, stop heating, and add the curing agent after it drops to room temperature, stir evenly, and discharge the material to obtain the electrolyte-resistant adhesive.
2. The electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries according to claim 1, characterized in that: The preparation method of the double-sided tape comprises the following steps: The first step is to use a precision coating machine to apply the electrolyte resistant adhesive on one side of the PET base film layer, and control the coating amount to 10-15g / cm 2 , then placed in an oven, controlled at 100-120°C, wait for the adhesive to solidify to form a film layer, and then attach non-silicon release paper to the outside of the film layer to form a release film; In the second step, the same operation as in the first step is performed on the other side of the PET base film layer to obtain a double-sided tape.
3. The electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries according to claim 1, characterized in that: The specific preparation method of the cross-linking agent comprises the following steps: Step S1, nitrogen is introduced into the polymerization kettle, and then 2,2-bis(4-hydroxycyclohexyl)hexafluoropropane and toluene are added, stirring is started, and then di-tert-butylchlorosilane is added into the polymerization kettle. After the addition is completed, the temperature is increased to 70-80° C., and after stirring for 1-3 hours, an acid binding agent is added into the polymerization kettle, and stirring is continued for 8-12 hours. The solvent is evaporated, and the temperature is lowered and the material is discharged to obtain an intermediate polymer; Step S2, adding the intermediate polymer and the terminal modifier into tetrahydrofuran, stirring mechanically, and then adding the phase transfer catalyst, and then raising the temperature to 60-70°C, stirring at the temperature for 2-4 hours, cooling and discharging the material, and the crosslinking agent can be obtained.
4. The electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries according to claim 3, characterized in that: In step S1, the molar ratio of 2,2-bis(4-hydroxycyclohexyl)hexafluoropropane to di-tert-butylchlorosilane is 1:0.8-0.
9.
5. The electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries according to claim 3, characterized in that: In step S1, the acid binding agent is triethylamine.
6. The electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries according to claim 3, characterized in that: In step S2, the terminal group modifier is glycidyl methacrylate or glycidyl acrylate.
7. The electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries according to claim 3, characterized in that: In step S2, the phase transfer catalyst is boron trifluoride ether complex.
8. The electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries according to claim 1, characterized in that: The initiator is azobisisobutyronitrile or azobisisoheptanenitrile.
9. The electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries according to claim 1, characterized in that: The organic solvent is ethyl acetate or toluene.
10. The electrolyte-resistant double-sided adhesive tape for environmentally friendly new energy lithium batteries according to claim 1, characterized in that: The curing agent is an aziridine curing agent or an isocyanate curing agent.
Citation Information
Cited By
Corrosion-resistant power-on viscosity-reducing adhesive tape and preparation method thereof
CN121471837A
Corrosion-resistant conductive adhesion-reducing tape and method of making same
CN121471837B